Fostering Intercultural Communication in Primary Education: Designing Two-Dimensional (2D) Dialogic Reading Materials for Online Classroom - Sabilah, Fardini; Rifah, Lailatul (FKIP Universitas Lampung, 2024)
Abstract: Fostering Intercultural Communication in Primary Education: Designing Two-Dimensional (2D) Dialogic Reading Materials for Online Classroom. Objectives: Within the ongoing process of globalization, intercultural communication has been identified as one of the key competences of the 21st century. In the context of Primary Education, intercultural communication can be defined as the “ability to communicate effectively and appropriately in intercultural situations based on one’s intercultural knowledge, skills, and attitudes” (Deardorff, 2006). Methods: The design of this research is Research and Development (R & D) by using 4D (Define, Design, Develop and Disseminate. There are two kinds of questionnaire that will be used in the Define step, they are: (1) needs analysis questionnaire, and (2) expert judgment questionnaire. Findings: The needs analysis questionnaire is distributed to the English teachers in Primary Education to identify the target needs and the learning needs of the students. The expert judgment questionnaire is used to evaluate the Dialogic Reading material. The data from the needs analysis questionnaire will be analyzed using frequency and percentage and the results are then will be used as the basis to design and develop the materials, while the data from the expert judgment questionnaire were analyzed using descriptive statistics. Conclusion: The integration of intercultural contents with dialogic reading with CROWD questions formula is good online material that can boost primary school students to learn English better. It is recommended that further researcher can create another topic of Dialogic Reading which is more up to date, interesting in its’ illustration or pictures and more advance in the digital technology, for example in the form of 3 or 4-dimensional animation. Keywords: intercultural communication, dialogic reading, english for young learners.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202425